Theoretical, Methodological and Empirical Issues in Studying Change - Pettigrew, A (1987)
Book reviewed in this article Pettigrew, A. M. The Awakening Giant: Continuity and Change in ICI THEORETICAL, METHODOLOGICAL, AND EMPIRICAL ISSUES IN STUDYING CHANGE:[1] A RESPONSE TO STARKEY